Mapping the Regulatory Framework for Telemedicine in Zambia: A Content Analysis - Muyunda, Lillian; Mpundu, Mubanga (International Journal of Membrane Science and Technology, 2024)
This paper explores the regulatory framework for telemedicine in Zambia. Telemedicine, involving remote clinical services using technology, is a rapidly evolving field intersecting with legal, ethical, and professional domains. The primary aim is to understand Zambia's telemedicine regulatory framework through an analysis of key documents namely the Zambia E-Government Interoperability Standard (eGIF), Zambia Digital Health Strategy 2022-2026, HPCZ Guidelines for the Quality Assurance of Telemedicine Services, and Statutory Instrument 43 of 2023 (SI 43 of 2023). The study addresses the challenge of comprehensively understanding and effectively implementing telemedicine in Zambia, considering the evolving nature of technology and healthcare services. Mapping the regulatory framework is a critical exercise for ensuring legal compliance, maintaining high standards of service, protecting patients, and making informed strategic decisions in the telemedicine sector. The study conducts a detailed exploration and content analysis of the aforementioned documents. This includes examination of their contributions to establishing a strong telemedicine landscape in Zambia, focusing on aspects like interoperability, data security, and healthcare service delivery. Findings reveal each document's significant, yet varied, contributions to the telemedicine framework in Zambia. The eGIF ensures integrated, standardized, and secure digital telemedicine services. The Zambia Digital Health Strategy 2022-2026 promotes telemedicine via digital technology and global alignment, while the HPCZ Guidelines provide a detailed framework focusing on ethical and legal standards. SI. 43 of 2023 emphasizes data security, quality assurance, and collaboration in telemedicine. Comparatively, Zambia's framework, as shaped by the four documents, aligns with global standards but differs in its centralized regulation and strategic focus, lacking extensive coverage on medical device regulations and reimbursement issues seen in other countries. The study suggests the need for a unified approach to telemedicine, emphasizing standardization, legal compliance, accessibility, and inclusivity. Recommendations include improving interoperability, ensuring data security, and fostering user-centric telemedicine services for enhanced healthcare outcomes.